2021
DOI: 10.1001/jamainternmed.2020.7071
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Electronic Health Record Use Between US and Non-US Health Systems

Abstract: IMPORTANCE Understanding how the electronic health record (EHR) system changes clinician work, productivity, and well-being is critical. Little is known regarding global variation in patterns of use. OBJECTIVE To provide insights into which EHR activities clinicians spend their time doing, the EHR tools they use, the system messages they receive, and the amount of time they spend using the EHR after hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 43 publications
3
98
3
Order By: Relevance
“…Finally, we only included physician participants practicing in the United States. Given known differences in EHR use and regulatory structures in other countries, these results might differ if examined in other healthcare systems [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we only included physician participants practicing in the United States. Given known differences in EHR use and regulatory structures in other countries, these results might differ if examined in other healthcare systems [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Clinicians in the United States spend significantly more time per day actively using the EHR and performing four clinical activities: notes, orders, in-basket messages, and clinical review, a reflection of this documentation burden. 10,11 Time spent on EHR has been identified as an important unit of measure of attenuated efficiency in use of health care provider clinical time, which is a high-cost and limited resource and may be associated with reduced patient satisfaction. 12,13 Time motion studies and EHR log records have indicated an increase in time allocated for desktop medicine with physicians spending nearly 2 hours in the EHR and on other desk work for every hour of direct patient care.…”
Section: Background and Significancementioning
confidence: 99%
“…12,13 Time motion studies and EHR log records have indicated an increase in time allocated for desktop medicine with physicians spending nearly 2 hours in the EHR and on other desk work for every hour of direct patient care. 11,[14][15][16][17][18] This perhaps contributes to overflow of EHR work into the physician's nonclinical and personal time, negatively affecting work-life balance. 19 There is accumulating evidence indicating the association of EHR use after work hours with occupational distress including burnout.…”
Section: Background and Significancementioning
confidence: 99%
“…Growing deployments of Electronic Health Records (EHRs) systems have established large practice-based longitudinal patient records causing an increase in the volume of unstructured data (80%) in the currently available health care records [ 1 ]. Inefficient and ineffective use of EHRs due to overwhelming volume has led to physician burnout (70% of clinicians reported health information technology [HIT]-related stress) due to increased workload during their limited (e.g.,15–20 min) clinic visit [ 2 5 ]. The application of Artificial Intelligence (AI) to health care may potentially address these challenges through AI-assisted clinical decision support (CDS) tools.…”
Section: Introductionmentioning
confidence: 99%